Investigation of the Effects and Degradation Mechanism of Low-oxygen on the Stability of Blueberry Anthocyanins in Juice Simulation system - Zhouyang SHENG; Gengsheng XIAO; Lijuan ZHANG; Yujuan XU; Jijun WU; Yuanshan YU; Tenggen HU; Bo ZOU (Guangdong nongye kexue)
【Objective】Anthocyanins are a class of natural water-soluble pigment, which is easy to be oxidized and degraded during processing and storage. The study aims to investigate the effect of low-oxygen conditions on the stability of anthocyanin in the simulated system of fruit juice, in hopes of providing a theoretical basis for improving the stability of anthocyanin in fruit juice.【Method】Four individual anthocyanins of blueberries (Cy-gal: cornflowerin-galactoside, Pn-glu: paeoniflorin-glucoside, Pn-ara: paeoniflorin-arabinose glycoside, Ma-gal: mallowin-galactoside) were adopted as research objects, and a citric acid buffer saline solution simulation system (pH=3.0, close to the blueberry juice system) was prepared to study the changes of anthocyanins in the juice simulation system during storage at 37℃ under nitrogen-inflated (low oxygen group) and non-nitrogen-inflated (conventional group) conditions. The effects of different metal ions, ascorbic acid, and phenolic acids under low oxygen and conventional conditions on anthocyanins were compared. Finally, high-performance liquid chromatography-triple quadrupole mass spectrometry tandem analysis was used to detect the degradation products of anthocyanins.【Result】During the storage of simulated system, the content of all four anthocyanosides decreased continuously. After 40 d of storage, the loss rates of Cy-gal, Ma-gal, Pn-ara, and Pn-glu in conventional group were 72.28%, 58.76%, 47.73%, and 59.54%, respectively, while the loss rates of low-oxygen group decreased to 66.44%, 47.85%, 44.09%, and 52.72%, respectively, which were significantly lower than those in the conventional group. In addition, low-oxygen conditions reduced the destructive effects of Zn2+ and ascorbic acid on anthocyanin. Comparative analysis revealed that the degradation products of paeoniflorin under conventional conditions were mainly quercetin and vanillic acid, whereas the major degradation products of paeoniflorin in low-oxygen environment were vanillic acid and coumarin derivatives, and the degradation products of cornflowerin were protocatechuic acid regardless of oxygen conditions.【Conclusion】Low oxygen conditions have a protective effect on four anthocyanins in the juice simulation system, and can alleviate the damage of metal ions and ascorbic acid to anthocyanins. The mechanism is related to the change in the degradation pathway of anthocyanins.